Juice Powders from Rosehip (Rosa canina L.): Physical, Chemical, and Antiglycation Properties - Aleksandra Hendrysiak; Jessica Brzezowska; Nancy Nicolet; Dimitri Bocquel; Wilfried Andlauer; Anna Michalska-Ciechanowska (Molecules, 2023)
Fruits from rosehip (Rosa canina L.) are gaining popularity due to their content and profile of bioactive components. Rosehip is distinct for its antioxidant, immunomodulatory, and anticancer properties. However, the abundance of these bioactives led to a tart taste, resulting in its consumption mainly in processed form. Due to microbiological safety, pasteurization is the preferred way of processing, which affects the chemical properties of the juice. A promising approach to improve acceptability of rosehip’s physical properties, while preserving its bioactive compounds and adding health-promoting benefits, is to enrich the rosehip juice with functional carriers before drying. The influence of the carrier type (maltodextrin, inulin, trehalose, palatinose) and drying technique (spray- and freeze-drying) on the physical, chemical, and antioxidant properties of pasteurized, and non-pasteurized juice powders was examined in this study. In addition, the ability of powders with functional carriers to inhibit protein glycation was evaluated. Spray drying led to products with improved physical properties in relation to freeze-drying. The addition of carrier substances significantly influenced the antioxidant capacity determined by TEAC ABTS and FRAP methods, whereby the application of inulin and palatinose retained antioxidant capacity better than the frequently used maltodextrin. Moreover, rosehip juice powders showed a promising ability to inhibit protein glycation.